Test and Simulation Validation of Gear Transmission Error - Yongchao Yuan; Ziling Wang; Zhongming Liu; Li Yu; Haiming Gang (Jixie chuandong)
Based on the dynamic measurement method of grating， a set of gear transmission error measurement and data processing device and system are established to realize the precise measurement of gear transmission error. According to the forming process principle， an accurate finite element analysis model including gear assembly error， manufacturing error and modification is created， then the process of simulation test is conducted， and the simulation results and test data are compared to verify the correctness of the finite element model.